PENYIDIKAN TERHADAP MASSA PELAKU TINDAK PIDANA MAIN HAKIM SENDIRI (EIGENRICHTING) DI KEPOLISIAN RESOR KUANTAN SINGINGI - Andre Gunawan; Erdianto Erdianto; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Eigenrichting is a form of violation of the rule of criminal law, because it is an act committed by an unauthorized person and is carried out according to their own will which is contrary to the law. This condition will not emerge by itself, because basically people do not want to commit violence, but because there are things that force them to take vigilante actions, there are various forms of vigilante action. In this case, Vigilante Crimes often occur in the jurisdiction of the Kuantan Singingi Police, where these cases occur almost every year resulting in cases continuing without clarity from the reporting party. In 2015 there were 8 cases, 6 cases were resolved with 15 suspects. In 2016 there were 5 cases and 2 cases were resolved with 10 suspects. In 2017 there were 13 cases, 5 cases were resolved with 13 suspects. In 2018 there were 7 cases and 5 cases were resolved with 12 suspects. then in 2019 there were 17 cases and 11 cases were resolved with 24 suspects. And in 2020 there were 6 cases and 6 cases were resolved with 12 suspects.This research uses empirical legal research or sociological legal research. The samples in this study were the Head of the Kuantan Singingi Police Criminal Investigation Unit, the Kuantan Singing Police Criminal Investigation Unit, Community and Community Leaders. The analytical tool in this research is a qualitative way. This study found that there are things that are not optimal in reality in the field, so it is necessary to anticipate with maximum effort.This study concludes that the investigation of the mass who committed the crime of vigilantism at the Kuantan Singi police resort has not been running optimally. This is reinforced, as almost every year vigilante crime occurs and the case continues without any clarity from the reporting party. In addition, there are several obstacles in the field, such as the limited number of police in the Kuantan Singingi Resort, inadequate coordination between one law enforcement apparatus and another, and local cultural factors that are less participatory in legal developments.Keywords: Main Judge Alone Crime – The crowd - Kuantan Singingi Police